Rethinking social exclusion the end of the social? - Winlow, Simon 1972-; Hall, Steve 1955- (SAGE, 2013)
This is an impassioned and controversial book from two leading sociologists in the field of social exclusion. They argue that social exclusion is not simply seen in ghettos or sink estates, but also in exclusive gated housing developments, the vacuous non-places of the shopping mall, the deadening reality of low-level service work, and in the depressing uniformity of our political parties
Keywords: Marginalität